A Study of Solid Waste Generation in Residential College UNIMAS West Campus as Potential Renewable Energy - Mohd Azrin, Mohd Said; Bush Engat, Ritchie (JASPE, 2014)
Solid waste management has become a critical issue faced by Malaysia due to the country’s rapid development, both in population and economic. The same goes to the tertiary education institutions, which also faced by Universiti Malaysia Sarawak, (UNIMAS). UNIMAS is a hostel provided campus, where the human traffic is considerably high. Everyday large amount of solid waste are produced by the residents of UNIMAS. Statistic data and percentage of solid waste produced by UNIMAS residents according to type have never been investigated. Therefore this study provides an insight of this kind of data for the purpose of future development in UNIMAS solid waste management. The type of solid waste produced by Residential College UNIMAS West Campus and its percentages and volume produced are discussed focusing on the solid waste that have potential energy value and recyclable materials. The data in terms of percentage and approximate amount of volume was applied in the calculation of the potential energy of the solid waste recovery according to the types. The result shows that the total potential amount of energy from solid waste produced by Residential College UNIMAS West campus could reach up to 14027.19 kJ/kg where the highest value that is 22.64% of energy content was contributed by Tun Ahmad Zaidi College.